Appraisal of Safety and Security as part of Tourist Destination Management in Cape Coast-Elmina-Kakum area in Ghana (Academic Journal of Internal Affairs, 2020)
Tourists’ safety and security have now become essential condition for the travel and tourism industry in the world. Ghana as a peaceful tourist destination in the sub-Saharan Africa relies and rakes in huge foreign exchange from tourism promotion. The tourism hub in the Central Region of Ghana was chosen as the case study area: Cape Coast destination area. The purpose of the study was to examine tourists’ perception of safety and ascertain if tourists would recommend the destination to other potential tourists. Purposive sampling technique and questionnaires were used. Most of the respondents rated their overall perception of tourists’ safety at the destination as safe. However, it was observed that safety installations in these facilities were either not working or non-existent and there was no supervision, evaluation or repairs of these installations. It is recommended that a team of tourism experts should be formed as a supervisory body to help monitoring the tourists’ safety and security in tourist facilities and destinations in the region.
Keywords: safety; tourism promotion; destination; Cape Coast-Elmina- Kakum